Research Priorities for FCTC Articles 20, 21, and 22: Surveillance/Evaluation and Information Exchange - Giovino, Gary A. (Oxford University Press, 2013)
INTRODUCTION: Framework Convention on Tobacco Control (FCTC) Articles 20, 21, and 22 call for strong monitoring and reporting of tobacco use and factors influencing use and disease (Articles 20 and 21) and for collaboration among the Parties and relevant organizations to share resources, knowledge, and expertise on all relevant tobacco control strategies (Article 22). METHODS: This paper provides background information and discusses research strategies that would strengthen these efforts and better inform the Parties. By necessity, Articles 20 and 21 are discussed separately from Article 22, although 1 example that relates to both 20/21 and 22 is discussed at the end. RESULTS: Twelve important research opportunities on surveillance and evaluation are recognized, along with 4 on collaboration. The authors believe that the 6 most important areas for research would study (a) possible underreporting of tobacco use among certain demographic groups in some countries, (b) measures of industry activities, (c) optimal sampling strategies, (d) sentinel surveillance, (e) networks of tobacco companies and their partners as they promote tobacco use and interfere with implementation of the FCTC, and (f) network/relationship factors that impact diffusion of knowledge and decision making on the implementation of the FCTC. In addition, we call for a review process of existing surveillance and evaluation strategies to coordinate activities to make optimal use of existing resources. This activity would involve networking as prescribed in Article 22. CONCLUSIONS: Studies and activities such as these would facilitate control of the tobacco epidemic.